Analisis Prediktor Transisi Peserta Didik Kelas X SMK Negeri 1 Sungai Raya Kabupaten Kubu Raya - Yanto, Heri Apri; Purwaningsih, Endang; Okianna, Okianna (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine family interest and socio-economic factors as predictors of the transition of students choosing to enter school at SMK Negeri 1 Sungai Raya, Kubu Raya Regency. This research uses a qualitative approach with descriptive methods. Data collection techniques used in-depth interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that: 1. The interest factor is a predictor of students' transition to school at State Vocational School (SMK) 1 Sungai Raya, Kubu Raya Regency, with sub factors: a). there is a feeling of joy in choosing a vocational school, b). there is a concentration of attention and thoughts towards vocational school, c). a willingness to learn, d). there is a desire from within to enter vocational school, e). There are efforts being made to realize the desire to enter vocational school. 2. Family's socio-economic status as a predictor of school transition at SMK Negeri 1 Sungai Raya, Kubu Raya Regency with sub-factors: a). the parents' education on average is mostly elementary school (SD) graduates, junior high school (SMP) and senior high school (SMA) graduates and there are also a small number of bachelor's degree (S1) graduates; b). the jobs of the students' parents mostly work as farmers and gardeners and porters; c). His parents' income is also around IDR 500,000/month and his parents' income is around IDR 500,000. 2,000,000 per month. So it can be concluded that interest and family socio-economic factors can be predictors of students' transition to choosing a school at SMK Negeri I Sungai Raya Kubu Raya